Realita Seni Bela Diri Kuntau Banjar di Era Modernisasi - Mazid, Nurhalis; Budhi, Setia (Huma: Jurnal Sosiologi, 2024)
Kuntau Banjar is an indigenous traditional martial art in the life of the people of South Kalimantan, whose existence is currently threatened by modernization that erodes local cultural values. This study aims to determine the reality of the Banjar kuntau martial art in Pemakuan Village, Sungai Tabuk Sub-district, Banjar Regency in the face of modernization. This research was analyzed using Talcott Parsons' functional structural theory. The research method used is descriptive qualitative. The data collection used observation, interview and documentation. The research was conducted from October 2022 to March 2023. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The results of this study show that the survival of the Banjar kuntau martial art in the era of modernization is threatened with extinction and loss of existence in the community. Currently, the martial art of kuntau is increasingly marginalized, less attractive to the younger generation which has an impact on the lack of regeneration. People, especially young people, even know less about kuntau martial arts today. This reality has led to the loss of values contained in the Banjar kuntau martial art, namely social values, moral values, and religious values. Therefore, the Banjar government and community, as well as other related parties, must to make strategic efforts to preserve and develop the kuntau martial art as one of the cultural identities of the Banjar tribe.